2007
DOI: 10.1634/stemcells.2007-0440
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Cancer Stem Cells in MMTV-Wnt-1 Murine Breast Tumors

Abstract: Orthologs of these differentially expressed genes predicted survival of human breast cancer patients from two different study groups. These studies suggest that there is a cancer stem cell compartment in the MMTV-Wnt-1 murine breast tumor and that there is a clinical utility of this model for the study of cancer stem cells. STEM CELLS 2008;26:364 -371 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
239
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(262 citation statements)
references
References 49 publications
13
239
3
4
Order By: Relevance
“…Breast CSCs were also identified in MMTV-Wnt1 mice by the expression of CD24 and Thy1 (Thy1 has been used as a stem cell marker in other tissues and organs). When profiled, these cells produced a signature that was similar to published MaSC gene expression signatures [76]. Other global gene expression profiling analyses suggested that the mouse MaSC signature correlated with not only the MMTV-Wnt1 tumors, but also p53 -/-tumors [28].…”
Section: Much Of This Evidence Fits Into the Paradigm Of Tumorinitiatsupporting
confidence: 59%
“…Breast CSCs were also identified in MMTV-Wnt1 mice by the expression of CD24 and Thy1 (Thy1 has been used as a stem cell marker in other tissues and organs). When profiled, these cells produced a signature that was similar to published MaSC gene expression signatures [76]. Other global gene expression profiling analyses suggested that the mouse MaSC signature correlated with not only the MMTV-Wnt1 tumors, but also p53 -/-tumors [28].…”
Section: Much Of This Evidence Fits Into the Paradigm Of Tumorinitiatsupporting
confidence: 59%
“…The number of cells that are terminally differentiated is increasing over time, reaching a steady level that is comparable to normal growth, see Figure 6. Note that in both normal and benign tumor cases, the total stem cell population consisting of quiescent and progenitor populations is 5%, which is in agreement with experimental values, see [1], [4], [10].…”
Section: Disease Progression and Model Predictionssupporting
confidence: 89%
“…In breast cancer, Cho et al (39) showed that cells displaying the CD90 1 /CD24 1 /CD49f 1 /CD45 2 immunophenotype, identified in MMTV-wnt-1 murine breast tumors, were highly enriched for cells, which were able to form tumors when transplanted into syngeneic recipients. In humans, Donnenberg et al (40) demonstrated that breast tumors contain a small population of CD44 1 /CD90 1 localized at the tumor periphery, adjacent to the CD90 1 stroma.…”
Section: Discussionmentioning
confidence: 99%